The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10479-018-3062-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of promotional cost sharing on the decisions of two-level supply chain with uncertain demand

Abstract: In much of today's competitive marketplace, consumers have the opportunity to choose where they spend their money based on their examination of a company's corporate social responsibility (CSR). A company's social reputation and its promotional efforts may influence consumer choice. Sustainable development is highly regarded by governments, experts, decision-makers and managers in organizations and two-level supply chains. This supply chain includes a manufacturer (acting as leader) and a retailer (acting as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Our work is also related to the literature on advertising in the market, for example, Chutani and Sethi (2018); He et al (2009); Servaes and Tamayo (2013); Taleizadeh et al (2020); Thomas (2020) and Zhang et al (2020). design various advertising schemes in which the manufacturer-controlled advertising scheme can lead to a higher advertising intensity, and the retailer-controlled advertising scheme can bring a lower wholesale price.…”
Section: Advertisingmentioning
confidence: 99%
“…Our work is also related to the literature on advertising in the market, for example, Chutani and Sethi (2018); He et al (2009); Servaes and Tamayo (2013); Taleizadeh et al (2020); Thomas (2020) and Zhang et al (2020). design various advertising schemes in which the manufacturer-controlled advertising scheme can lead to a higher advertising intensity, and the retailer-controlled advertising scheme can bring a lower wholesale price.…”
Section: Advertisingmentioning
confidence: 99%
“…They found that under certain conditions, a price-dependent base stock policy is optimal on the both backorder and lost-sale cases. Taleizadeh et al [40] investigated the effect of cost of advertisement and promotional cost sharing on the coordination of a two-echelon supply chain considering under uncertain demand. Yadav et al [49] proposed a non-cooperative Stackelberg game model in a two-level supply chain with imperfect quality and allowable shortage.…”
Section: Introductionmentioning
confidence: 99%
“…The supply chain considering the triple bottom line including economic, environmental and societal dimensions of sustainability plays a vital role in achieving Sustainable Development Goals. Even though the area of sustainable supply chain management (SSCM) has received much attention from both quantitative and empirical modelling researchers within the last two decades, the research into the development of practical decision-making tools and frameworks for manufacturing supply chain sustainability is still evolving (Korpela et al 2001;Soheilirad et al 2017;Taleizadeh et al 2018). Seuring and Müller (2008) provided critical attributes of sustainable supply chain management by identifying the simultaneous consideration of economic, environmental and social impacts of the supply chain.…”
Section: Introductionmentioning
confidence: 99%